Knowledge of the utilization of telegram for learning among primary students in Kuantan - Saadiah Awang, Salim; Noor Azida, Sahabudin; Murugiah, Gausallyaa; Nur Shamsiah, Abdul Rahman; Norhasyimah, Hamzah (Institute of Electrical and Electronics Engineers Inc., 2023)
There are various online learning platforms already available such as Google Classroom, Coursera, Skillshare and Udemy. In this regard, the Ministry of Education Malaysia (MOE) has launched a learning platform, Digital Educational Learning Initiative Malaysia (Delima). This platform offers all the digital applications and services needed by teachers, and students in the Malaysian school system. However, the use of Delima did not get the response as expected. Telegram can be seen as one of the effective platforms for students in online learning to support these efforts. The focus of this study is to identify the utilization of Telegram for learning among primary students, to determine the factors that influence the utilization of Telegram among primary students and determine students' perceptions of Telegram as a learning platform. This quantitative study was conducted by conducting a questionnaire to 361 primary students aged 11 to 12 years around Kuantan, Pahang. The TAM model was used in this study. The study results show nine factors influence students' utilization of Telegram in learning: usefulness, usability, accessibility, ELearning Attitude, functionality, enjoyment, subjective norms, behavioral intentions, and actual use. The results showed that the utilization of Telegram for learning based on the factors that have been identified is in the range of 57% to 72%. With this, the utilization of Telegram as a learning tool can increase productivity, performance, and thus motivation to primary school students.